2015
DOI: 10.1111/jphp.12473
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mechanisms are involved in antidepressant-like effects of bisbenzylisoquinolines liensinine and its analogs isolated from the embryo of Nelumbo nucifera Gaertner seeds in mice

Abstract: These data suggest that liensinine and isoliensinine from Nelumbo nucifera Gaertner have antidepressant-like effects and that antidepressant-like effects of liensinine and its analogues are closely related to serotonergic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…Because AD is highly associated with ChEs and BACE1 activities, inflammation, and oxidative stress, N. nucifera can be considered as a preventive measure to inhibit the progression of AD. Using different in vivo animal models, Jung et al demonstrated the requirement of anti-oxidant, antiinflammatory, and the inhibitory effects of neferine (Tomita et al, 1962;Kunitomo et al, 1973;Liu et al, 2006) 8 Norarmepavine Leaves, Seeds (Kupchan et al, 1963;Duan et al, 2014) 9 Bromo methyl armepavine Leaves, Seeds (Rai et al, 2006) 10 Methoxymethy lisoquinoline Leaves, Seeds (Rai et al, 2006) 11 Lotusine Embryo, Seeds, Fruit Wang et al, 1991) 12 Higenamine Plumule (Zhou et al, 2013) (Chao et al, 1962;Furukawa et al, 1965;Guo and Chen, 1984;Chen et al, 2007b;Furukawa, 1966) 19 Isoliensinine (Isolie) Seeds, Fruit, Embryo (Tomita et al, 1965;Chen et al, 2007b;Furukawa, 1966) 20 Neferine Seeds, Fruit, Embryo (Chen et al, 2007a;Zhou et al, 2013;Sugimoto et al, 2015;Zhang et al, 2015b;Furukawa, 1966) Fruits and seeds (Toyoda, 1966;Mukherjee et al, 1997aMukherjee et al, , 1997b 189Asparagine…”
Section: Pharmacological Reportsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because AD is highly associated with ChEs and BACE1 activities, inflammation, and oxidative stress, N. nucifera can be considered as a preventive measure to inhibit the progression of AD. Using different in vivo animal models, Jung et al demonstrated the requirement of anti-oxidant, antiinflammatory, and the inhibitory effects of neferine (Tomita et al, 1962;Kunitomo et al, 1973;Liu et al, 2006) 8 Norarmepavine Leaves, Seeds (Kupchan et al, 1963;Duan et al, 2014) 9 Bromo methyl armepavine Leaves, Seeds (Rai et al, 2006) 10 Methoxymethy lisoquinoline Leaves, Seeds (Rai et al, 2006) 11 Lotusine Embryo, Seeds, Fruit Wang et al, 1991) 12 Higenamine Plumule (Zhou et al, 2013) (Chao et al, 1962;Furukawa et al, 1965;Guo and Chen, 1984;Chen et al, 2007b;Furukawa, 1966) 19 Isoliensinine (Isolie) Seeds, Fruit, Embryo (Tomita et al, 1965;Chen et al, 2007b;Furukawa, 1966) 20 Neferine Seeds, Fruit, Embryo (Chen et al, 2007a;Zhou et al, 2013;Sugimoto et al, 2015;Zhang et al, 2015b;Furukawa, 1966) Fruits and seeds (Toyoda, 1966;Mukherjee et al, 1997aMukherjee et al, , 1997b 189Asparagine…”
Section: Pharmacological Reportsmentioning
confidence: 99%
“…In addition, total alkaloids from lotus leaf showed sedative hypnotic effect by increasing the brain level of GABA (Yan et al, 2015). Liensinine, isoliensinine, and neferine isolated from the embryo of N. nucifera seeds have been reported to elicit anti-depressant-like effects in mice after the forced swimming test (Sugimoto et al, 2015). In another study, treatment of allantoin from N. Nucifera in scopolamine-treated mice increased the expression levels of phospho PI3K, AKT, and GSK to improve the cognitive function observed in AD (Ahn et al, 2014).…”
Section: Pharmacological Reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NO-scavenging activity of neferine was consistent with the previous report. 13 Moreover, the direct NO-scavenging effects of three alkaloids are weaker than that of NO production by LPS-activated microglial cells (Fig. 2), which indicated that the direct NO-scavenging effects are likely to be one of the mechanisms of these alkaloids to decrease the NO level in culture supernatant uids of LPSactivated microglial cells.…”
Section: 27mentioning
confidence: 99%